Evaluating Virtual and Local Pepper Presence in the Role of Communicator Interacting with Another Human Presenter at a Vocational Fair of Computer Sciences - Romero Pérez, Samantha (2022)
This paper proposes the evaluation of the local and remote interaction of a Pepper Robot and a human presenter answering questions from high-school students at the Universidad de Costa Rica’s vocational fair. The interactions were presented in two: 1) a group interacted locally in the same room 2) a group interacted remotely via online meeting. Within a sample of 18 Costa Rican high-school students, this study assessed criteria such as: perceived enjoyment, intention to use, perceived sociability, trust, intelligence, animacy, anthropomorphism, and sympathy, utilizing testing tools such as Unified Theory of Acceptance and Use of Technology (UTAUT) and Godspeed Questionnaire (GSQ). These instruments identified significant differences during the interaction in the perceived sociability and anthropomorphism in both scenarios. Suggesting different relevant information regarding the perception of the interaction with the robot and perception of the robot itself in both cases.